Capital Market Regulation Through Accounting Standards: A Critical Examination in Light of Fiqh Mu’āmalah (Islamic Economic Jurisprudence) - Kurmanbekova Aziza; Rana Ahmed Majeed; Asaad Hamdi Muhammad; Fawzi Hussain Mohammed; Rozhgar Khorsheed Mahmud; Eman Abdel Moneim Mal Allah; Hadeel Saadoon Maarij; Ahmed Kalel Hasan Alzarkany; Nazim Younus Saleh (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article critically explores the impact of accounting standards on capital market regulation and highlights the extent to which they align with the principles of Islamic economic jurisprudence. Accounting standards are key instruments for promoting transparency, comparability, and accountability in financial reporting, which are central to traditional banking and Islamic finance. Using a mixed-methods approach encompassing empirical analysis, case studies, and a comparative framework, this study examines the effectiveness and limitations of accounting standards and practices in promoting fair and stable capital markets. The results indicate that international accounting standards have significantly enhanced investor confidence, liquidity, and market efficiency; however, several obstacles remain. This also applies to underlying factors, such as high implementation costs, inadequate enforcement of rights, and limited application, which often ignore the socio-ethical dimensions of Sharia (such as justice (ʿadl), public interest (maslahah), and uncertainty (gharar)). Furthermore, due to the subjectivity involved in financial reporting, a fair presentation of transactions may not always be apparent. This contradicts the Islamic requirements of full disclosure and fair dealing